2020
DOI: 10.12659/msm.920351
|View full text |Cite
|
Sign up to set email alerts
|

Synaptotagmin 12 (SYT12) Gene Expression Promotes Cell Proliferation and Progression of Lung Adenocarcinoma and Involves the Phosphoinositide 3-Kinase (PI3K)/AKT/Mammalian Target of Rapamycin (mTOR) Pathway

Abstract: Background: This study aimed to use bioinformatics analysis to compare data from tissue microarrays from patients with lung adenocarcinoma (LUAD) and normal lung tissue, and human lung adenocarcinoma cells with normal lung epithelial cells in vitro to investigate the role of synaptotagmin 12 (SYT12) gene expression in LUAD. Material/Methods: Human lung adenocarcinoma cell lines (A549, SPC-A-1, H1299, H1975, and PC9) and the normal HBE cell line were compared, and tumor xenografts were developed in mice. The Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…5C). Vimentin 35,36 and SLUG 3 have been commonly used as EMT markers, as the previous study has shown to be correlated to tumor metastasis and cancer resistance toward drug treatment, while the clinical study has shown ICAM1, 37 FBP1, 38-40 SYT12, 41 and INHBE 42,43 to be related to poor prognosis, proliferation, invasiveness, and migratory properties of lung cancer; the MMP family of MMP13 and MMP14 has shown different trends with upregulation of MMP14 44,45 expression and downregulation of MMP13 46 expression while both have been identified to be related to the malignancy of lung cancer; SERPINE1 47,48 has been known to increase proliferation and tumor budding and inhibit apoptosis in primary tumors; S1003A 49 plays a role in regulating retinoic acid alpha that is found to promote tumor progression in several other cancers; TXNIP 50,51 plays a role in metabolic reprogramming and oxidative stress of cancer cells that can act as a tumor suppressor gene. Although our discovery shows a possibility of using iMSCs as a potential treatment for cancer, participation from other cells and functional systems is required for a better understanding.…”
Section: Discussionmentioning
confidence: 99%
“…5C). Vimentin 35,36 and SLUG 3 have been commonly used as EMT markers, as the previous study has shown to be correlated to tumor metastasis and cancer resistance toward drug treatment, while the clinical study has shown ICAM1, 37 FBP1, 38-40 SYT12, 41 and INHBE 42,43 to be related to poor prognosis, proliferation, invasiveness, and migratory properties of lung cancer; the MMP family of MMP13 and MMP14 has shown different trends with upregulation of MMP14 44,45 expression and downregulation of MMP13 46 expression while both have been identified to be related to the malignancy of lung cancer; SERPINE1 47,48 has been known to increase proliferation and tumor budding and inhibit apoptosis in primary tumors; S1003A 49 plays a role in regulating retinoic acid alpha that is found to promote tumor progression in several other cancers; TXNIP 50,51 plays a role in metabolic reprogramming and oxidative stress of cancer cells that can act as a tumor suppressor gene. Although our discovery shows a possibility of using iMSCs as a potential treatment for cancer, participation from other cells and functional systems is required for a better understanding.…”
Section: Discussionmentioning
confidence: 99%
“…To discover a gene that associates with PTC that could differentiate low-risk and high-risk PTC patients, we send 39 paired PTC samples for RNA sequencing and discovered that SYT12 was overexpressed in PTC tissues associated with nearby non-neoplastic thyroid tissues. There are a few reports about SYT12, and it has been found that played a crucial role in some cancers such as oral cancer and lung adenocarcinoma [10,11]. Jonklaas et al also showed that SYT12 could predict papillary thyroid cancer outcomes in a prospective cohort [12].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, variants of the human SYT12 were shown to be associated with some cancers [10,11]. Liu et al reported that SYT12 acted as a possible oncogene by activating the PI3K-AKT-mTOR signal channel in lung adenocarcinoma [11].…”
Section: Ivyspringmentioning
confidence: 99%
See 1 more Smart Citation
“…SYT12 also promoted LUAD cell proliferation and migration in vitro and increased the weight and volume of tumors in mice xenograft models. In parallel, SYT12 could activate the PI3K/AKT/mTOR 10.3389/fmed.2022.968081 signaling pathway by increasing the level of phosphorylation of PIK3R3 (39).…”
Section: Syt12mentioning
confidence: 99%